1998
DOI: 10.1007/s003830050264
|View full text |Cite
|
Sign up to set email alerts
|

Rectal biopsy for Hirschsprung's disease: what is the optimum method?

Abstract: During a 3-year period, 258 infants and children underwent rectal biopsy to exclude Hirschsprung's disease (HD) and related disorders; 32 (12%) were found to have HD. Major morbidity occurred in 3 (2%) of 148 patients undergoing rectal suction biopsy (RSB) and 22 (13%) of 168 suction biopsies were inadequate for diagnosis. In 102 children over 6 months of age, Storz rectal cup biopsy forceps were used with no significant morbidity and adequate biopsies were obtained in 96% of cases. Open rectal biopsy was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 0 publications
3
78
2
1
Order By: Relevance
“…In our series, 14.5% of patients had inadequate biopsies containing insufficient amount of submucosa for a proper diagnosis. This rate is in accordance with what other authors have reported, with percentages of inadequate biopsies ranging from 11.6 to 26% [6,[39][40][41]. To overcome the problem of insufficient material for a proper diagnosis, we always took three biopsies per patient.…”
Section: Discussionsupporting
confidence: 88%
“…In our series, 14.5% of patients had inadequate biopsies containing insufficient amount of submucosa for a proper diagnosis. This rate is in accordance with what other authors have reported, with percentages of inadequate biopsies ranging from 11.6 to 26% [6,[39][40][41]. To overcome the problem of insufficient material for a proper diagnosis, we always took three biopsies per patient.…”
Section: Discussionsupporting
confidence: 88%
“…Persistent rectal bleeding requiring blood transfusion occurred in approximately 0.5 % of all included RSBs [12,13,34,50,56,59,62,64]. Rectal perforation [12,13] and pelvic sepsis [12,13,36] have each been reported in less than 0.1 % of cases. Rectal perforation seemed to be more probable in newborns and infants as demonstrated by the presence of portions of circular muscle layer in this age-related group compared with older patients.…”
Section: Discussionmentioning
confidence: 98%
“…Inadequate tissue samples result in a diagnostic delay with need for repeat RSBs or full-thickness rectal biopsies, thus causing considerable parental anxiety, prolonged hospital stay and increased costs [11]. Although very rare, there have been a few articles reporting on serious RSB-related adverse events such as severe rectal bleeding and bowel perforation, which in turn add further risk to the patient [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…If a full-thickness biopsy is obtained, this could be done as low as 1 cm above the dentate line because the myenteric plexus extends more distally. Between 9% and 30% of RSBs are inadequate and must be repeated, primarily because of insufficient submucosa in the biopsy (21)(22)(23). This is particularly a problem in children older than 1 year.…”
Section: Investigations Histopathologymentioning
confidence: 99%